The Human Side of Factory Automation: Managerial and Human Resource Strategies for Making Automation SucceedThe Human Side of Factory Automation: Managerial and Human Resource Strategies for Making Automation Succeed, by MajchrzakAnn. San Francisco: Jos-sey-Bass. 1988, 390 pp., $29.95, hard-back. - Lancaster, Kenneth (Academy of Management Review, 1990)
The article presents a review of the book ?The Human Side of Factory Automation: Managerial and Human Resource Strategies for Making Automation Succeed,? by Ann Majchrzak.